European eel (Anguilla anguilla) recruitment in Comacchio lagoon (Italy) data ... - Gavioli, Anna; Milardi, Marco; Lanzoni, Mattia; Aschonitis, Vassilis; Castaldelli, Giuseppe (Zenodo, 2024)
This dataset was managed for the aims of the project ECOSISTER (Ecosystem for Sustainable Transition in Emilia-Romagna), WP3 of Spoke 5 and provides information about the captured glass eels entering in the Comacchio Lagoon (NE Italy), one of the most important coastal wetlands in Europe for biodiversity conservation and one of the most important places for eels fishery. To capture glass eels entering in the Comacchio Lagoon, four sampling sites (Foce, Bellocchio, Gobbino and Passo Pedone sites were selected at gateways or canals, which directly connect the lagoon to the sea. Environmental and meteorological variables are also provided. The dataset is provided in two formats: - Microsoft Excel XLSX file, including 3 sheets (Dataset, Fields and units, Taxonomy) - CSV files (UTF-8), 3 files corresponding to the 3 sheets of the Excel file The dataset includes 59 CPUE data for different sampling dates and sampling locations. Glass eels sampling was performed from 19/01/2011 to 7/4/2011. All the dataset fields ...